2021
DOI: 10.3389/fpsyt.2021.762041
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Care for Pregnant Women and Parents With Methamphetamine-Related Mental Disorders

Abstract: Background: Methamphetamine use is a rapidly increasing cause of morbidity and mortality. Pregnant women and new parents who consume methamphetamine are at high risk since they seldom seek health services despite having multiple needs. We addressed this care gap by implementing an easily accessible program that pools resources from psychiatric, obstetric, and pediatric departments as well as community and government agencies.Method: This real-life observational study evaluated an integrated care program in 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…In humans, loss of the KIRREL3 gene was associated with neurodevelopmental disorders, such as Jacobson’s syndrome, intellectual disability, and autism spectrum disorder ( Bhalla et al, 2008 ). Knockout of the Kirrel3 gene in mice led to auditory sensory and motor skill impairment and ADHD (attention deficit and hyperactivity disorder) ( Hisaoka et al, 2018 ), as well as an increased risk of ADHD in children following prenatal METH exposure ( Pendergast et al, 2012 ; Petzold et al, 2021 ). Lrpprc is a leucine-rich PPR motif-containing protein, and mutation of the LRPPRC gene may lead to Leigh syndrome in French Canadians ( Mootha et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, loss of the KIRREL3 gene was associated with neurodevelopmental disorders, such as Jacobson’s syndrome, intellectual disability, and autism spectrum disorder ( Bhalla et al, 2008 ). Knockout of the Kirrel3 gene in mice led to auditory sensory and motor skill impairment and ADHD (attention deficit and hyperactivity disorder) ( Hisaoka et al, 2018 ), as well as an increased risk of ADHD in children following prenatal METH exposure ( Pendergast et al, 2012 ; Petzold et al, 2021 ). Lrpprc is a leucine-rich PPR motif-containing protein, and mutation of the LRPPRC gene may lead to Leigh syndrome in French Canadians ( Mootha et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric comorbidities and social complexities were frequent in our naturalistic sample of pregnant and parenting women, echoing the multiple burdens reported in association with methamphetamine use ( 19 , 24 ). We previously found that comorbid attention-deficit hyperactivity disorder and depression jeopardized treatment engagement in integrated care ( 27 ). Yet in contrast to social challenges, psychiatric comorbidities were not significantly related to housing at discharge.…”
Section: Discussionmentioning
confidence: 99%
“…We studied all 102 women who accessed psychiatric care within Mamadam since its start in 2016 and left or completed treatment before July 30, 2020. This naturalistic sample included the 73 women whose treatment adherence was previously analyzed ( 27 ). Adherence was categorized as early discontinuation (before implementing a care plan), partial completion of the program (late discontinuation), or successful completion (requiring stable abstinence).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in the study had needs across multiple domains, encompassing physical and mental health needs, income support, social support and justice involvement. This need for is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) integrated care to support the whole of a person's health needs through effective working across healthcare and other services has also been highlighted by other studies with people with substance use disorders (Petzold et al, 2021;Savic, Best, Manning, & Lubman, 2017).…”
Section: Integrated and Structurally Competent Service Deliverymentioning
confidence: 99%